Nonvariceal upper gastrointestinal bleeding - Contardo Zambrano, Carlos (2024)
Diagnostic and treatment aspects of non variceal upper gastrointestinal bleeding are still a challenge for the Gastroenterologist. Peptic ulcer disease remains the main cause of bleeding, accounting for 50 % of cases in the medical literature. Dieulafoy lesion and some special types of ulcer bleeding produce severe forms of active upper GI hemorrhage. Less severe bleeding is due to Mallory – Weiss esophageal tears, gastritis, esophagitis, angiodysplasia and the so called watermelon stomach. Angiodysplastic lesions are the main source of chronic gastrointestinal bleeding. Novel treatments, specifically therapeutic endoscopy for high risk bleeding stigmata, profound acid suppression with proton pump inhibitors and intensive care of these patients in specialized units have significantly reduced the rate of bleeding recurrence, the need for blood transfusions, surgical interventions and days of hospitalization. According to recent papers mortality has been reduced from 10 % to 2,3 – 5,4 %.